Health information management: principles and organization for health information services - Skurka, Margaret A (J-B AHA Press, 2012)
This is the fifth edition of the definitive reference source on the management of health records. Health Information Management provides the basic guidelines on content and structure, analysis, assessment, and improvement of information critical to every health care organization. This thoroughly revised and updated edition reflects the significant changes in the field and the most current and successful practices most notably, the computerization of record operations and systems, and of the record itself.